2018
DOI: 10.3389/fpsyg.2018.02242
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Virtual Hand Illusion and Motor Performance

Abstract: Bodily self-consciousness consists of agency (i.e., the feeling of controlling one’s actions and causing external events) and body ownership (i.e., the feeling that one’s body belongs to one’s self). If a visual presentation of a virtual (fake) hand matches the active movement of a real hand, both the agency and body ownership of the virtual hand are induced [i.e., the active virtual hand illusion (VHI)]. However, previous active VHI studies have rarely considered the effects of goal-related movement errors (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 39 publications
4
26
0
Order By: Relevance
“…Ownership is mainly determined by the realism of the fake body part (Argelaguet et al, 2016 ) and the temporal match between the perceived visual and tactile stimulation (Tsakiris and Haggard, 2005 ; Tsakiris, 2010 ; Kalckert and Ehrsson, 2012 ), whereas agency primarily arises from the match between predicted (intended) movements and actual kinesthetic feedback (i.e., the perceived efficiency of control: Frith et al, 2000 ; Argelaguet et al, 2016 ; Braun et al, 2018 ). This becomes manifest in the virtual hand illusion (VHI), where ownership is mostly determined by delays (temporal mismatches between visual and tactile stimulation; Ismail and Shimada, 2016 ; Shibuya et al, 2018 ), while agency is determined both by delays and by movement variability (visual-motor mismatches; Shibuya et al, 2018 ). Functional Magnetic Resonance Imaging (fMRI) studies have shown that ownership and agency are linked to different brain areas.…”
Section: The Sense Of Embodimentmentioning
confidence: 99%
“…Ownership is mainly determined by the realism of the fake body part (Argelaguet et al, 2016 ) and the temporal match between the perceived visual and tactile stimulation (Tsakiris and Haggard, 2005 ; Tsakiris, 2010 ; Kalckert and Ehrsson, 2012 ), whereas agency primarily arises from the match between predicted (intended) movements and actual kinesthetic feedback (i.e., the perceived efficiency of control: Frith et al, 2000 ; Argelaguet et al, 2016 ; Braun et al, 2018 ). This becomes manifest in the virtual hand illusion (VHI), where ownership is mostly determined by delays (temporal mismatches between visual and tactile stimulation; Ismail and Shimada, 2016 ; Shibuya et al, 2018 ), while agency is determined both by delays and by movement variability (visual-motor mismatches; Shibuya et al, 2018 ). Functional Magnetic Resonance Imaging (fMRI) studies have shown that ownership and agency are linked to different brain areas.…”
Section: The Sense Of Embodimentmentioning
confidence: 99%
“…Previous research on VEs employed several tools, such as a two-joint mechanical arm 16 , joysticks 9 , and pinch force sensors 15 , which showed improvement in the motor learning ability. These experiments were performed using sensory information as clues instead of visual information, like the arm-reaching task used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual hand illusion (VHI) was also used in motor learning owing to its applicability and expandability. Several studies have reported that motor learning is promoted even in VEs 9,15,16 . In addition, a previous study has suggested that post-training performance in virtual and real training is equivalent and both of which signi cantly exceeds without training 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, pairing of motor efferent signals with perceived sensory consequences may also affect the rubber hand illusion, such as in the moving and virtual Rubber Hand illusions [ 51 , 133 , 134 , 135 , 136 , 137 , 138 ]. The relation between the role of efferent motor and afferent sensory signals to the incorporation process has been recently cast in the perspective of Bayesian sensory filtering through predictive coding [ 139 ].…”
Section: Incorporating Tools In the Ppsmentioning
confidence: 99%